Profissão do lar: imposição ou escolha? - (:unkn) unknown (Universidade Federal do Pampa, 2018)
The purpose of this study was to investigate who are the subjects who left paid jobs in the labor market in order to become household professionals, by analyzing the main reasons for such an attitude and its implications for gender, domestic and family issues. Methodologically, this study is characterized as descriptive-exploratory, with a qualitative approach, and it is carried out by using the thematic oral history method. In order to select its subjects, this study used the snowball sampling, and the research scenario was initially limited to the city of Santana do Livramento, Brazil. Data were collected between the months of August and October 2017, through semi-structured interviews, with an average duration of 1 hour each, carried out with thirteen household professionals, of whom nine were women, and four were men. Data were examined through discursive textual analysis. Classified in order of decreasing importance, the results reveal that the reasons why the interviewees abandoned permanently or temporarily the labor market were: small children, unemployment, elderly and/or ill relative, husband, job hassle, city changing, the feeling of homesickness, doubled working hours and the high cost of living in the capital. These reasons differ among the interviewees by age, by social and marital situations, by the economic context, by levels of education and by the working relationships. By disaggregating the main reasons as imposition/choice and by gender, the following information were observed: women (imposition: unemployment, husband; choice: maternity, small children), men (imposition: unemployment; choice: city change). These results reveal that the men and women interviewed left the labor market because of completely different reasons – only having unemployment as a common feature. It was found that the men and the women interviewed execute the same household chores, however, in the domestic and familiar spheres, them (the women) face more difficulties in sharing these chores with their husbands and/or with their male children. Household chores consume a great deal energy and a great part of the time of the interviewees – being greater for the women (4.6 hours a day, 32.2 hours a week) than for the men (3.6 hours a day, 25.2 hours a week) and are characterized by fragmentation, multiplicity and simultaneity. Beyond the gender, color, level of education, the family monthly income, the family type of arrangement, the age and the number of children and the presence of household appliances consist in variables that directly affect the distribution of time dedicated to do the household chores in the private sphere, revealing gender inequalities. Domestic work is perceived, by the interviewees, especially the women, as an unpaid, invisible and devalued activity of the private sphere, both by their families and by society. The reasons for this situation are deeply related to the role played by the woman, which is based on a patriarchal society and on the notion of work elaborated by the capitalist system. It is important, therefore, to think about ways of valuing the unpaid household chores in the Brazilian society, one of which is the accounting of domestic chores in the Gross Domestic Product (GDP) through the construction of satellite accounts. As long as official national research continues to adopt a capitalist vision of work, the domestic work, and whoever does it, especially women, will remain devalued and invisible in the private and in the social spheres.
Household Profession: imposition or choice?
Keywords: Gênero; Trabalho doméstico não remunerado; Trabalho reprodutivo; Esfera privada; Afazeres domésticos; Gender; Unpaid Domestic Work; Reproductive Labor; Private Sphere; Household Chores; CNPQ::CIENCIAS SOCIAIS APLICADAS